Gestational weight gain counselling practices among different antenatal health care providers: a qualitative grounded theory study - Beth Murray-Davis; Howard Berger; Nir Melamed; Karizma Mawjee; Maisah Syed; Jon Barrett; Joel G. Ray; Michael Geary; Sarah D. McDonald; for DOH-NET (Diabetes, Obesity and Hypertension in Pregnancy Research Network) (BMC, 2020)
Abstract Background Inappropriate gestational weight gain in pregnancy may negatively impact health outcomes for mothers and babies. While optimal gestational weight gain is often not acheived, effective counselling by antenatal health care providers is recommended. It is not known if gestational weight gain counselling practices differ by type of antenatal health care provider, namely, family physicians, midwives and obstetricians, and what barriers impede the delivery of such counselling. The objective of this study was to understand the counselling of family physicians, midwives and obstetricians in Ontario and what factors act as barriers and enablers to the provision of counselling about GWG. Methods Semi-structured interviews were conducted with seven family physicians, six midwives and five obstetricians in Ontario, Canada, where pregnancy care is universally covered. Convenience and purposive sampling techniques were employed. A grounded theory approach was used for data analysis. Codes, categories and themes were generated using NVIVO software. Results Providers reported that they offered gestational weight gain counselling to all patients early in pregnancy. Counselling topics included gestational weight gain targets, nutrition & exercise, gestational diabetes prevention, while dispelling misconceptions about gestational weight gain. Most do not routinely address the adverse outcomes linked to gestational weight gain, or daily caloric intake goals for pregnancy. The health care providers all faced similar barriers to counselling including patient attitudes, social and cultural issues, and accessibility of resources. Patient enthusiasm and access to a dietician motivated health care providers to provide more in-depth gestational weight gain counselling. Conclusion Reported gestational weight gain counselling practices were similar between midwives, obstetricians and family physicians. Antenatal knowledge translation tools for patients and health care providers are needed, and would seem to be suitable for use across all three types of health care provider specialties.